UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN DENGGUNAKAN MODEL PEMBELAJARAN VAN HIELE PADA TOPIK EGIEMPAT DI KELAS XI RPL (REKAYASA PERANGKAT LUNAK) SMK NEGERI 9 JAYAPURA TAHUN AJARAN 2017/2018 - Suzana Weyai; Bettisari Napitupulu; Jonner Nainggolan (Sekolah Tinggi Pariwisata Mataram, 2021)
Weyai, Suzana 2018. “The Efforts of Improving the results of Learning Using a Learning Model Van Hiele on the topic Quadrilateral in class XI RPL (Software engineering) SMK Negeri 9 Jayapura Academic year 2017/2018”. Thesis. Master of Mathematics Education Study Program of the Faculty of Teacher Training and Educational Sciences of the University of Cenderawasih. Supervisor (1) Dr. Bettisari Napitupulu, M. Sc. (2) Dr. Jonner Nainggolan, M. Si. This research approach was qualitative research with this type of class action research, data collected in the form of test result pre Cycle, the research was done in two cycles and at each end of the cycle is evaluations and test. The result of the study participants in the measure through final test cycle I and cycle II. The study was conducted in this research is a study based on the stage of the van Hiele thinking method that began with stage 0 (visualization), stage I (analysis), to stage II (informal deduction) through the phase information, orientation, explanation, free orientation, and the phase of integration on a sub chapter of parallelogram, rectangle, square, rhombus, quadrilateral, and trapezoid. Learning is conducted in the form of group discussions using LKK and media of instructions. There are two LKK used, namely: (1) LKK 1 contains definitions and properties of rectangles and LKK 2 contains the circumference and area of a quadrilateral. With the application of the learning model based on the stage of the van Hiele method, average value and yiels learning learners increased. From the result of the implementation of the material with the cycle 1 data obtained 20 learners (100%) reach the complete study with an average rating of 84.1 and classes of implementation material B cycle 1 retrieved 12 people (75%) reach the complete study with and a average rating of class 85.75.